Quality of Life after Surgical Treatment for Esophageal Atresia: Long-Term Outcome of 154 Patients - Hölscher, Alice Catherine; Laschat, Michael; Choinitzki, Vera; Zwink, Nadine; Jenetzky, Ekkehart; Münsterer, Oliver; Kurz, Ralf; Pauly, Marcus; Brokmeier, Ulrike; Leutner, Andreas; Ure, Benno; Lacher, Martin; Schumacher, Johannes; Reutter, Heiko; Boemers, Thomas Michael (European Journal of Pediatric Surgery, 2017)
Background The short- and long-term surgical results in patients with esophageal atresia (EA) with or without tracheoesophageal fistula (TEF) have been described in depth from a physician's perspective. Contrarily, the perception and coping strategies of affected patients and their parents have rarely been reported. The aim of this study was to generate data on this matter.Patients and Methods A total of 154 patients who had operative reconstruction for EA between 1971 and 2012 were evaluated for demographic data, surgical technique, affection of daily life, and coping strategies.Results Gastroesophageal reflux (GER) symptoms were reported in 59% of cases with 33% requiring fundoplication. Regular bougienages of anastomotic strictures were necessary in 68% with 36% requiring repeated dilatations in the first postoperative year. Enteral nutrition via a nasogastric tube was performed in 66% after surgery. In 40%, the tube was needed until their sixth week of life. In 25%, nutritional support was necessary more than 1 year out of surgery. Quality of life in general was felt to be impaired according to the patients' parents in 50%. Regarding medical advice about long-term morbidities, more than 50% of the parents felt insufficiently advised. There were no statistical differences between the EA/TEF subtypes regarding GER symptoms, frequency of esophageal dilatations, eating behaviors, or support of the parents in feeding management.Conclusion Our observations indicate that a high percentage of EA/TEF patients and families require more intensive aftercare and support during the first year following primary reconstruction than previously thought. We observed a higher need for adequate parental information on long-term complications of their children compared with current practice.
Keywords: esophageal atresia; tracheoesophageal fistula; quality of life